Development and validation of a natural dynamic facial expression stimulus set - Borges Bastos Pasqualette, Laura Beatriz; Klinger, Sara; Kulke, Louisa (PLoS ONE, 2023)
Emotion research commonly uses either controlled and standardised pictures or natural video stimuli to measure participants’ reactions to emotional content. Natural stimulus materials can be beneficial; however, certain measures such as neuroscientific methods, require temporally and visually controlled stimulus material. The current study aimed to create and validate video stimuli in which a model displays positive, neutral and negative expressions. These stimuli were kept as natural as possible while editing timing and visual features to make them suitable for neuroscientific research (e.g. EEG). The stimuli were successfully controlled regarding their features and the validation studies show that participants reliably classify the displayed expression correctly and perceive it as genuine. In conclusion, we present a motion stimulus set that is perceived as natural and that is suitable for neuroscientific research, as well as a pipeline describing successful editing methods for controlling natural stimuli.
CRIS-Team Scopus Importer:2023-07-21